2021
DOI: 10.1055/s-0041-1735822
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Recognition, and Response to Stroke among the General Public—An Observational Study

Abstract: Objective To evaluate awareness and response to stroke among the general public. Materials and Methods In this prospective, observational study, self-reported stroke awareness questionnaire was administered in 2000 consecutive participants who visited outpatient clinic of a tertiary care hospital. For data analysis, comparison included for awareness of stroke and response in case of stroke. Results The average age of the study participants was 39.64 ± 15.55 (17–85), with 651(32.6%) women. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
4
9
1
Order By: Relevance
“…The low knowledge of the types of strokes, noted in the present study (cerebral arterial infarction score: 2%; intracerebral hemorrhage score: 2.2%), is lower than that reported in the India study (cerebral arterial infarction score: 39.3%; intracerebral hemorrhage score: 13.4%) [43].…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The low knowledge of the types of strokes, noted in the present study (cerebral arterial infarction score: 2%; intracerebral hemorrhage score: 2.2%), is lower than that reported in the India study (cerebral arterial infarction score: 39.3%; intracerebral hemorrhage score: 13.4%) [43].…”
Section: Discussioncontrasting
confidence: 93%
“…Concerning other warning signs, low knowledge is noted (score < 16%) (Table 2). This is also observed in previous series (score < 40%) [28] [39] [43] [49]- [55].…”
Section: Discussionsupporting
confidence: 89%
“…There have been many studies about knowledge of stroke amongst stroke patients and the general population. 24…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies about knowledge of stroke amongst stroke patients and the general population. [2][3][4] However, there is a paucity of data regarding knowledge about diagnosis, aetiology, investigations, and management of stroke (acute ischemic stroke/intracranial hemorrhage, and cerebral venous sinus thrombosis) amongst neurologists in general and particularly from India.…”
Section: Introductionmentioning
confidence: 99%
“…4,13-18, 30-32, 34-35, 38 Large scale national studies have found that the ability to recognise stroke symptoms has not improved despite numerous public awareness campaigns. 42,43 Smaller regional studies have reported increased public knowledge of risk factors for stroke and increased ability to recognise stroke symptoms. 26,27 A 90 minute education intervention aimed at middle aged men and women increased stroke knowledge in two semi-rural communities in Ireland.…”
Section: Introductionmentioning
confidence: 99%